DOP52 Development of a host-microbe interaction workflow to reveal the cell- and condition-specific effects of a commensal bacteria upon IBD. (21st January 2022) - Potari-gul, L; Modos, D; Fonseca, S; Madgwick, M; Thomas, J P; Sudhakar, P; Booth, C; Stentz, R; Carding, S R; Korcsmaros, T
Abstract: Background: Humans are colonized by complex microbial communities which contribute to physiological processes in the host. The communication between microbes and host is crucial to maintain the homeostasis and gut health. Disruption in the microbiome composition leads to increased inflammation and appearance of diseases, such as inflammatory bowel disease (IBD). Interspecies interaction prediction combined with gene expression patterns on individual cell level by single-cell omics data reveals a new insight into the molecular background of cell-type specific host-microbe interactions. Methods: Previously we developed the MicrobioLink pipeline (Andrighetti et al, Cells, 2020), an in silico microbe-host protein-protein interaction prediction algorithm. Here, we implemented a computational workflow based on MicrobioLink to predict and compare the cell-specific effects of a commensal bacteria in healthy and diseased conditions using a publicly available single-cell RNAseq dataset (Smilie et al, Cell, 2019) from colon biopsies describing 51 cell types - including fibroblasts, epithelial and immune cells - in healthy, non-inflamed and inflamed ulcerative colitis (UC). With functional analysis, microbe-affected processes have been discovered, while reliable network biology resources, such as OmniPath and Reactome, were used to identify the direct mechanism of action of the bacterial molecules. Results: Demonstrating the applicability of the new computational workflow, we analysed the effect of a common gut commensal bacteria - Bacteroides thetaiotaomicron (Bt) - on human immune cells focusing on the Toll-like receptor (TLR) signalling. We found that extracellular vesicles (EVs) secreted by Bt may be able to modulate the TLR pathway intracellularly. The analysis highlighted that Bt targets differ among cells and between the same cells in healthy versus UC conditions. The in silico findings were validated in EV-monocyte co-cultures demonstrating the requirement for TLR4 and Toll-interleukin-1 receptor domain-containing adaptor protein (TIRAP) in EV-elicited NF-kB activation. Conclusion: The current pipeline offers potentially interesting connection points and detailed mechanistic insight containing mechanistic information about microbe-host interactions. This information can be tested and harnessed to understand better how microbial proteins may be of therapeutic value in inflammatory diseases, such as IBD.